A Review of the Empirical Literature on Meaningful Work: Progress and Research Agenda. (March 2019) - Bailey, Catherine; Yeoman, Ruth; Madden, Adrian; Thompson, Marc; Kerridge, Gary
Meaningful work is a topic of importance in core domains of human resource development (HRD) such as employee engagement, motivation, and personal development. However, there is little consensus over what comprises meaningful work or concerning the antecedent and outcome factors associated with meaningfulness. Prior theorizing has tended to conflate conceptual and empirical arguments, and hence, we lack clear insight into factors related to employees' experience of meaningfulness. To address these gaps, we undertook an analysis of the empirical literature relating to meaningful work. In all, 71 studies met the inclusion criteria. We focused on the question, "What is the empirical evidence base concerning meaningful work, and how can this inform theory and practice in HRD?" The synthesis revealed dominant trends alongside significant gaps in understanding. We highlight the practical implications of our analysis for the HRD field and propose avenues for future research on meaningfulness within HRD.